2004
DOI: 10.1099/mic.0.26437-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovicin HJ50, a novel lantibiotic produced by Streptococcus bovis HJ50

Abstract: A bacteriocin-producing strain was isolated from raw milk and named Streptococcus bovis HJ50. Like most bacteriocins produced by lactic acid bacteria, bovicin HJ50 showed a narrow range of inhibiting activity. It was sensitive to trypsin, subtilisin and proteinase K. Bovicin HJ50 was extracted by n-propanol and purified by SP Sepharose Fast Flow, followed by Phenyl Superose and Sephadex G-50. Treatment of Micrococcus flavus NCIB8166 with bovicin HJ50 revealed potassium efflux from inside the cell in a concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 32 publications
2
42
0
2
Order By: Relevance
“…Our previous studies showed that bovicin HJ50 is a type AII (lacticin 481 group) lantibiotic containing a specific disulfide bridge (43). The gene products of bovK and bovR in the bovicin HJ50 biosynthesis gene locus show significant sequence similarity to SalK and SalR, respectively, which are thought to compose a two-component system to regulate salivaricin A production (40).…”
mentioning
confidence: 99%
“…Our previous studies showed that bovicin HJ50 is a type AII (lacticin 481 group) lantibiotic containing a specific disulfide bridge (43). The gene products of bovK and bovR in the bovicin HJ50 biosynthesis gene locus show significant sequence similarity to SalK and SalR, respectively, which are thought to compose a two-component system to regulate salivaricin A production (40).…”
mentioning
confidence: 99%
“…The disulfide bridge is rare in lantibiotics but was demonstrated here to be critical for suicin activity and has been previously underlined in bovicin HJ50 (35). A previous study showed that bovicin HJ50 could disrupt the membrane integrity of sensitive strain M. flavus NCIB8166, resulting in potassium efflux (45). Here, we found that suicin also disintegrated the cell membrane of M. flavus NCIB8166, leading to the disruption of membrane potential (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Bacteriocins produced by LAB such as Lactobacillus (12,25), Enterococcus (2,3,11,24,25), Leuconostoc (7,10), Streptococcus (22), and Carnobacterium (20,23) species have been frequently reported in previous studies. However, studies of bacteriocins from Weissella sp.…”
Section: Discussionmentioning
confidence: 99%